'Euro-Realism' in the 2014 European Parliament Elections: The European Conservatives and Reformists (ECR) and the Democratic Deficit. Issue 1 (2nd January 2016) - Steven, Martin
Abstract : The European Conservatives and Reformists (ECR) emerged as the third largest 'Euro-party' after the 2014 European elections, and are now well-positioned to perform a central role alongside the European People's Party and the Progressive Alliance of Socialists and Democrats in the eighth session of the European Parliament (EP). Despite this, relatively little is known about the views that ECR politicians represent, especially their core party ideology of 'Euro-realism'. In this article, it is argued that the development of ECR since 2009 is ultimately rooted in a central desire by its member party politicians to reform the European Union by addressing its 'democratic deficit' without destroying the wider integration project altogether. More widely, ECR is the most visible vehicle for 'soft' Euro-scepticism in the EP, promoting 'governance before policy'.